Wdrażanie różnojęzycznych studentów filologii regionów do czytania literatury francuskojęzycznej. Refleksja glottodydaktyczna nad wstępną koncepcją kursu - Orchowska, Izabela (Neofilolog, 2024)
The current paper is a reflection on introducing plurilingual students of Regional Language Studies to the reading of francophone literature. The paper first discusses the didactic background for the reflection and emphasizes the plurilingualism of students. Next, the author presents how the autonomization approach to learning and teaching could be applied in an optional course of French focused on developing plurilingual learners’ reading comprehension of francophone literary texts, even before they reach the advanced proficiency level in French. The initial course concept will be illustrated with didactic analysis of the francophone novel – “L’ignorance” by Milan Kundera.